PERGESERAN PERAN DAN FUNGSI ALUN-ALUN KALIWUNGU SEBAGAI RUANG TERBUKA PUBLIK - Lulut Indrianingrum; Anis Nur Azizah; Gilang Eko Prasetya; Nurul Hidayah (Jurnal Teknik Sipil dan Perencanaan, 2015)
Abstract: The existence of the square Kaliwungu very far from the characteristics of such a square. Not only the shape, but the function of the square has also shifted away. Although the existence as public space was still visible in the morning, but it the afternoon until evening, the square transformed into market. The function of the square as a public open space has been dominated as economic functions. From time to time the role of the square undergone many changes since the days of pre-colonial, colonial, post-colonial and current period. Changes in the role and function of the square as a public open space Kaliwungu basically occurs when the policy was issued regarding the transfer function around the market square into the parking lot of the mosque. It shows that the square as the center of the city has a strategic location that can not be separated from economic activities.